Social Capital and Political Participation in Lithuania - Imbrasaitė, Jūratė (Sociologija. Mintis ir veiksmas, 2004)
The wide resonance achieved by the notion of social capital among social scientists suggests that the term serve important purposes of analysis in current social thought. The focus of the study was the impact of social capital on political participation in Lithuania. The method of study was survey sample data and scientific literature analysis. The results of analysis reflects rather weak relationship between certain social capital dimensions and political participation, what could be a result of past communist legacy: persistence of friendship networks, closed nature of social networks, low level of interpersonal and institutional trust. Data analysis confirm an assumption that social capital dimensions have the bigger impact on collective political acts than on individual political acts. Membership in nongovernmental organizations has the biggest impact on collective political actions and it supports Putnam’s social capital theory. Frequency of conversations on political and social matters has the biggest impact on individual collective acts and rather low on collective acts.